Whole Genome Sequencing Analysis of Bacillus thuringiensis GR007 Reveals Multiple Pesticidal Protein Genes - Pacheco, Sabino; Gómez, Isabel; Chiñas, Marcos; Sánchez, Jorge; Soberón, Mario; Bravo, Alejandra (Frontiers in Microbiology, 2021)
Bacillus thuringiensis (Bt) are soil ubiquitous bacteria. They produce a great variability of insecticidal proteins, where certain of these toxins are used worldwide for pest control. Through their adaptation to diverse ecosystems, certain Bt strains have acquired genetic mobile elements by horizontal transfer, harboring genes that encode for different virulent factors and pesticidal proteins (PP). Genomic characterization of Bt strains provides a valuable source of PP with potential biotechnological applications for pest control. In this work, we have sequenced the complete genome of the bacterium Bt GR007 strain that is toxic to Spodoptera frugiperda and Manduca sexta larvae. Four replicons (one circular chromosome and three megaplasmids) were identified. The two largest megaplasmids (pGR340 and pGR157) contain multiple genes that codify for pesticidal proteins: ten cry genes (cry1Ab, cry1Bb, cry1Da, cry1Fb, cry1Hb, cry1Id, cry1Ja, cry1Ka, cry1Nb and cry2Ad), two vip genes (vip3Af and vip3Ag), two binary toxin genes (vpa2Ac and vpb1Ca), five genes that codify for insecticidal toxin components (Tc’s) and a truncated cry1Bd-like gene. In addition, genes that codify for several virulent factors were also found in this strain. Proteomic analysis of the parasporal crystals of GR007 revealed that they are composed of eight Cry proteins. Further cloning of these genes for their individual expression in Bt acrystalliferous strain, by means of their own intrinsic promoter showed expression of seven Cry proteins. These proteins display differential toxicity against M. sexta and S. frugiperda larvae, where Cry1Bb showed to be the most active protein against S. frugiperda larvae and Cry1Ka the most active protein against M. sexta larvae.